RAS based culture system for continuous production of Rotifers (Brachionus calyciflorus) in mass - FELIX, S; BHOSALE, MANGESH M; RAJAGOPALSAMY, C B T; ARUNA, S (The Indian Journal of Animal Sciences, 2020)
The present study was undertaken to find out preferred food type, minimum effective algal cell requirement, effective harvest rate of rotifers and to design and construct re-circulatory aquaculture system (RAS) based rotifer, Brachionus calyciflorus production system at Aquatic Rainbow Technology Park, Dr MGR Fisheries College and Research Institute, TNJFU, Madhavaram campus, Chennai during 2017–2019. In the first experiment, food types, viz. Chlorella vulgaris, Spirulina major, Scenedismus obliquus and Baker’s yeast were extensively fed to rotifers with control (5000 L). The highest rotifer count was observed with C. vulgaris food type (365.33±2.18 rotifers/ml) followed by Baker’s yeast (245.33±5.36 rotifers/ml) on 8th day which started declining gradually to 30th day because of lower water quality. Second experiment on algal consumption rate by rotifer postulated that 22,000–25,000 cells/day/rotifer was the minimum cell requirement. Third experiment on standardizing effective harvest rate (10%, 30%, 50% and 70%) suggested that daily harvest at 30% maintained the rotifer culture at its stationary phase (381±19.45 rotifers/ml). After the experiments, we have designed, built and operated RAS based live food production unit for 17 months where the harvested water was treated using series of filters (rapidsand, cartridge, UV filters) and reused for algal culture. The seasonal data showed that temperature plays a major role with the highest production during summer (404.43±24.33 rotifers/ml) and consequently lower in winter (301.21±14.33 rotifers/ml). The system opens a new perspective of commercial scale production of rotifers with standard culture and harvesting practices.